Formation of digital hygiene and cyberculture among future teachers of mathematics and informatics - Tóth Vivien; Товт Вівіен; Stoika Myroslav; Sztojka Miroszláv; Стойка Мирослав (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. The process of digitalization in Ukrainian education requires a profound reorientation of teacher training. Future teachers of mathematics and informatics must not only possess digital skills but also understand the ethical, safety, and cultural aspects of technology use. An essential component of modern teachers’ digital competence is the formation of digital hygiene and cyberculture, which determine their ability to interact safely, responsibly, and consciously in the digital environment [1]. Digital hygiene encompasses knowledge and skills related to personal data protection, information security, prevention of cyberbullying, and rational use of digital devices. According to Ş. Bayzan (2025), teachers’ level of cyber hygiene directly affects their awareness of digital security and reduces the risks of data breaches and manipulations [2]. For future teachers, this is especially important, as they act as intermediaries between technology and students. Cyberculture, in turn, is understood as a set of norms, values, and behavioral models in the virtual environment. It includes aspects of digital ethics, academic integrity, media literacy, and critical thinking. Developing cyberculture involves students’ ability to communicate consciously in online spaces, respect intellectual property, and avoid aggression or destructive interactions [3]. Research by Termenzhy (2025) emphasizes that cyberethics, cybersafety, and cybersecurity skills are core elements of AI-related competence for future educators. These skills should be integrated into the training of teachers in natural and mathematical sciences [4]. Domestic and international experience demonstrates that the formation of digital hygiene and cyberculture is effective only under a systemic approach, combining educational courses, practical trainings, independent activities, and research work [5]. As noted by Borysova (2023), the digital culture of future education should be based on conscious technology use, critical information evaluation, and social responsibility [5].
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: digital hygiene; teachers of mathematics; cyberculture; teachers of informatics